Emerging Adults’ Barriers, Consideration, and Intention to do Thalassemia Screening Test as Preventive Health Behavior - Yasmine Parawina Larasati; Adhityawarman Menaldi (Jurnal Psikologi, 2020)
The number of thalassemia patients in Indonesia is predicted to rise every year. This genetic disease could cause psychological impact and large expenses for patients, families, caretakers, and the government. This study aimed to analyze the correlation between perceived barriers (PB) and consideration of future consequences (CFC), and also their interaction with behavioral intention (BI) to undergo a thalassemia screening as part of preventive health behavior (PHB). Participants were 411 young adults, aged 18 to 25 years old (M = 20.47). The measurements used in the study were adapted versions of PHB Scale, the CFC-14 Scale, and BI Scale. Main results from PROCESS regression analysis showed, (1) a negative and significant influence from the PB to BI (b1 = -0.0089; p < 0.05), (2) CFC had insignificant influence toward BI (b2 = 0.0096; p > 0.05), (3) the interactions of PB and CFC had insignificant influence toward BI (b3 = -0.0005; p > 0.05). Self-efficacy, as controlled variable, had significant correlation with BI and became strong predictor toward the intention to enact PHB. This study concluded that barriers remain as dominant factor that determines someone's PHB. The more elaborate patient's knowledge, the more they see barriers as challenges, therefore the higher their efficacy to enact PHB.